Religion, spirituality, and aging: a social work perspective - Moody, Harry R. (Journal of gerontological social work, 2005)
Introduction : knowledge, practice, and hope / Harry R. Moody -- Research in spirituality, religion, and aging / David O. Moberg -- Religion, spirituality, and aging for "the aging" themselves / Henry C. Simmons -- Religion and coping in older adults : a social work perspective / Holly Nelson-Becker -- Religiosity as a mediator of caregiver well-being : does ethnicity make a difference? / Carmen L. Morano, Denise King -- "Religion is the finding thing" : an evolving spirituality in late life / Susan A. Eisenhandler -- Religious congregations as social service providers for older adults / Ram A. Cnaan, Stephanie C. Boddie, Jennifer J. Kang -- Guided by ethics : religion and spirituality in gerontological social work practice / Vicki Murdock -- Caregivers' use of spirituality in ethical decision-making / Terry L. Koenig -- Spirituality and social work in long-term care / Marty Richards -- Geriatric care management : spiritual challenges / Leonie Nowitz -- Postcards to God : exploring spiritual expression among disabled older adults / Mark Brennan, Sarah B. Laditka, Amy Cohen -- Creating sacred scenarios : opportunities for new rituals and sacred aging / Richard Address -- Culture change in long-term care : educating the next generation / Dwight Roth -- Autobiography as a spiritual practice / John-Raphael Staude -- Dreams for the second half of life / Harry R. Moody -- A pastoral understanding of positive aging / Samuel R. Seicol -- Land of forgetfulness : dementia care as spiritual formation / Wayne A. Ewing -- Caregiving and our inner elder : insights from a spiritual master / Richard Griffin -- Living with elder wisdom / Eugene Bianchi.